Differences in cerebral small vessel disease magnetic resonance imaging markers between lacunar stroke and non–Lobar intracerebral hemorrhage. (September 2021) - Wiegertjes, Kim; Jansen, Michelle G; Jolink, Wilmar MT; Duering, Marco; Koemans, Emma A; Schreuder, Floris HBM; Tuladhar, Anil M; Wermer, Marieke JH; Klijn, Catharina JM; Leeuw, Frank-Erik de
Introduction: It is unclear why cerebral small vessel disease (SVD) leads to lacunar stroke in some and to non–lobar intracerebral hemorrhage (ICH) in others. We investigated differences in MRI markers of SVD in patients with lacunar stroke or non–lobar ICH. Patients and methods: We included patients from two prospective cohort studies with either lacunar stroke (RUN DMC) or non–lobar ICH (FETCH). Differences in SVD markers (white matter hyperintensities [WMH], lacunes, cerebral microbleeds [CMB]) between groups were investigated with univariable tests; multivariable logistic regression analysis, adjusted for age, sex, and vascular risk factors; spatial correlation analysis and voxel–wise lesion symptom mapping. Results: We included 82 patients with lacunar stroke (median age 63, IQR 57–72) and 54 with non-lobar ICH (66, 59–75). WMH volumes and distribution were not different between groups. Lacunes were more frequent in patients with a lacunar stroke (44% vs. 17%, adjusted odds ratio [aOR] 5.69, 95% CI [1.66–22.75]) compared to patients with a non–lobar ICH. CMB were more frequent in patients with a non–lobar ICH (71% vs. 23%, aOR for lacunar stroke vs non–lobar ICH 0.08 95% CI [0.02–0.26]), and more often located in non–lobar regions compared to CMB in lacunar stroke. Discussion: Although we obserd different types of MRI markers of SVD within the same patient, ischemic markers of SVD were more frequent in the ischemic type of lacunar stroke, and hemorrhagic markers were more prevalent in the hemorrhagic phenotype of non-lobar ICH. Conclusion: There are differences between MRI markers of SVD between patients with a lacunar stroke and those with a non-lobar ICH.